Fragments of Romance - Riley, Christina (Romanticism on the Net, 2022)
Every few hours, the tide brings in treasure and takes it away, making the same beach new again, which I’m fairly certain is a large part of its appeal to me. It’s dizzying to think of all the ways the sea can touch a person, to the point that when asked what it means to me, my mind goes blank. Rather than using words, it feels more appropriate to hand over a pebble that’s been polished smooth by endless waves as if to say, like this. Or to show photograph after photograph of the ever-changing pattern of its surface. Like this.Where do you begin with something that has no beginning and no end? There’s barely enough time in one life to describe the colour of water, let alone what it holds.